The Effects of Green Transformational Leadership on The Green Behaviour of Business,The Environment and The Green Performance - Burcu Turan Torun (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2023)
The understanding of leadership which gives importance to green, that is, to the environment, today emerges as a green transformational leadership approach in the field of management and organization. The green transformational leadership approach is defined as a leadership model trying to protect the environment and providing the necessary behaviors along with the features which are covered by the transformational leadership approach. Green transformational leaders highlight the environmental values of the business, explain terms related to green business and aim to focus upon high-level environmental values. In the present study, it is probed to explain the meaning of green transformational leadership and how green behaviors of businesses make contribution to the environment and their performance and to contribute to the literature. Green transformational leadership is a leadership model which provides businesses an opportunity to solve problems related to their relationship and interaction with the environment and their impact upon economic performance. Namely, a transformational leader with green values motivates the followers and aims to provide organizational development by focusing on the issues which are beneficial to the organizational environment. Through the present study, it has been tried to draw a conceptual framework about green leadership and in this way make a contribution to the present literature. Although further studies on green transformational leadership which contributes to the emergence of green values are needed in the literature, it is thought that the present study, which aims to make a contribution to the literature theoretically, can shed light on related empirical studies.